Traumatic dental injuries and attention-deficit/hyperactivity disorder: is there a link? - SABUNCUOĞLU, OSMAN TALAT (WILEY, 2007)
Traumatic dental injuries (TDIs) constitute a major cause of morbidity among children worldwide. Both TDIs and attention-deficit/hyperactivity disorder (ADHD) are prevalent conditions with similar male-to-female predominance and similar age of presentation. While the commonest causes of TDIs have been identified as playground or sports accidents, a well-known feature of ADHD is accident proneness. Violence, another significant risk factor for TDIs, is more likely to be observed in conduct disorder, a common comorbidity of ADHD. Also, both TDIs and ADHD have been found to be associated with left-handedness. The presence of multiple dental trauma episodes (MDTE), as well as increased risk for non-dental injuries in children with TDIs indicates an underlying persistent condition, which resembles ADHD. Higher point prevalence of mental distress at age 30, found to be associated with increased lifetime prevalence of TDIs, may also be taken as an evidence of a background developmental disorder persisting into adulthood with various comorbidities. In conclusion, this review combines the results of several studies and explains the significance of ADHD as an underlying and predisposing factor for TDIs. Increased awareness and close collaboration between different disciplines involved are essential.
Keywords: dental trauma; tooth injuries; attention deficit hyperactivity disorder; DEFICIT HYPERACTIVITY DISORDER; PERMANENT INCISORS; ALCOHOL DEPENDENCE; SCHOOL-CHILDREN; RISK-FACTORS; PREVALENCE; ADOLESCENTS; TEETH; SCHOOLCHILDREN; LATERALIZATION